Nordeste : Docencia (Resistencia Universidad Nacional del Nordeste. Facultad de Humanidades)
Signatura: 0/03b
Existencia: 1995- 1; 1997- 2-4; 1998- 5-8; 1999- 9-10; 2000- 11; 2001- 12, 15; 2003- 16-18; 2009- 20
Keywords: Argentina; Ciencias Sociales; Nordeste